2010
DOI: 10.1245/s10434-010-0932-4
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Following Laparoscopy-Assisted Gastrectomy for Gastric Cancer: A Multicenter Retrospective Analysis of 1,417 Patients

Abstract: Background. The risk of recurrence and recurrence patterns after laparoscopy-assisted gastrectomy for gastric cancer remain unclear. The objective of this study is to assess recurrence and its timing, patterns, and risk factors following laparoscopy-assisted gastrectomy from multicenter data. Methods. A retrospective multicenter study was performed using data from 1,485 patients who had undergone laparoscopy-assisted gastrectomy for gastric cancer at ten institutions from 1998 to 2005. Recurrence and its timin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 36 publications
6
75
2
4
Order By: Relevance
“…The 5-year survival rate of 98.2% for both OS and RFS is comparable with that of previous retrospective studies assessing laparoscopic gastrectomy [10][11][12]. For open surgery, Nashimoto et al [13] Kim et al [12] reported the OS after matching for the operation method and surgeons did not show any significant differences between open gastrectomy and laparoscopic gastrectomy for all stages of cancer.…”
Section: Discussionsupporting
confidence: 72%
“…The 5-year survival rate of 98.2% for both OS and RFS is comparable with that of previous retrospective studies assessing laparoscopic gastrectomy [10][11][12]. For open surgery, Nashimoto et al [13] Kim et al [12] reported the OS after matching for the operation method and surgeons did not show any significant differences between open gastrectomy and laparoscopic gastrectomy for all stages of cancer.…”
Section: Discussionsupporting
confidence: 72%
“…23 Also, previous studies about surgery cases reported that the rate of recurrent gastric cancer within 2 and 3 years after gastrectomy were 68∼75% and 89∼90%, retrospectively. [24][25][26] Even though recurrent gastric cancer can be developed 5∼10 years after ESD, the median follow-up period of >3 years (37.2±23.6 months) was not short to identify the incidence of recurrent gastric cancer in young patients. However, to evaluate the overall and disease-specific survival rates for young patients with EGC after curative resection, a lifetime observation study is needed in this study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of surgeries involving gastrectomy with standard lymph node dissection have been carried out in South Korea and Japan (8,9). The results of randomized research allow us to conclude that gastrectomy has a number of advantages over conventional surgery; these are less blood loss and fewer complications, quicker patient recovery, fewer post-operative bed days, better visual effects, and almost the same 5-year survival rates at 57.3% vs. 58.9% (10)(11)(12).…”
Section: Minimally Invasive Treatment For Early Gcmentioning
confidence: 99%